Experimental Study on Active Interface Debonding Detection for Rectangular Concrete-Filled Steel Tubes with Surface Wave Measurement - Bin Xu; Lele Luan; Hongbing Chen; Jiang Wang; Wenting Zheng (Sensors, 2019)
Concrete-filled steel tube (CFST) members have been widely employed as major structural members carrying axial or vertical loads and the interface bond condition between steel tube and concrete core plays key roles in ensuring the confinement effect of steel tube on concrete core. An effective interface debonding defect detection approach for CFSTs is critical. In this paper, an active interface debonding detection approach using surface wave measurement with a piezoelectric lead zirconate titanate (PZT) patch as sensor mounted on the outer surface of the CFST member excited with a PZT actuator mounted on the identical surface is proposed in order to avoid embedding PZT-based smart aggregates (SAs) in concrete core. In order to validate the feasibility of the proposed approach and to investigate the effect of interface debonding defect on the surface wave measurement, two rectangular CFST specimens with different degrees of interface debonding defects on three internal surfaces are designed and experimentally studied. Surface stress waves excited by the PZT actuator and propagating along the steel tube of the specimens are measured by the PZT sensors with a pitch and catch pattern. Results show that the surface-mounted PZT sensor measurement is sensitive to the existence of interface debonding defect and the interface debonding defect leads to the increase in the voltage amplitude of surface wave measurement. A damage index defined with the surface wave measurement has a linear relationship with the heights of the interface debonding defects.